Intercultural Educational Guidance: Theoretical and Practical Approaches for its Understanding in Pluricultural Environments - Trejos-Morales, Carol Graciela (Revista Costarricense de Orientación, 2025)
Objective: To deepen the understanding and appreciation of cultural diversity, promoting the development of competencies that foster interculturality in pluricultural educational environments. Methodology: Based on an updated bibliographic review, the relationship between educational guidance and interculturality is analyzed, highlighting the importance of promoting mutual understanding and social cohesion. Results: The findings indicate that intercultural educational guidance is based on the premise that knowledge and appreciation of diverse cultures enrich individual and collective life, which overcomes stereotypes and prejudices. Furthermore, this perspective recognizes cultural diversity as a source of wealth that entails the responsibility to build more inclusive and respectful societies. To this end, emphasis is placed on implementing educational strategies such as the pedagogy of questioning and critical reflection, which are key to consolidating an intercultural educational guidance approach. This approach not only promotes equity and inclusion in educational settings, but also prepares individuals to face the challenges and seize the opportunities of a globalized world. Conclusions: In this sense, the role of the guidance professional is fundamental in promoting equity and social justice within educational settings. Their work involves guiding learning from an intercultural perspective and promoting awareness-raising and training processes that empower students, teachers, families, and communities to understand and respect diversity, thereby building more just and supportive communities enriched by values ​​that enhance social and cultural coexistence.